2022
DOI: 10.1039/d2cp02240k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of measured high-resolution doublet rovibronic spectra and related line lists of 12CH and 16OH

Abstract: Detailed understanding of the energy-level structure of the quantum states as well as of the rovibronic spectra of the ethylidyne (CH) and the hydroxyl (OH) radicals is mandatory for a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 182 publications
0
4
0
Order By: Relevance
“…The two lines near 365.6 nm are reproduced by resorting to the ExoMol [34] referenced molecular line lists, intensities and spectra (MoLLIST) [35] for the 12 C 1 H isotopologue of CH. However, analysis and establishment of high-resolution line lists of 12 CH continues to be of interest [36].…”
Section: Emission-and Cavity Ring-down-spectra Of the A-x And B-x Bandsmentioning
confidence: 99%
“…The two lines near 365.6 nm are reproduced by resorting to the ExoMol [34] referenced molecular line lists, intensities and spectra (MoLLIST) [35] for the 12 C 1 H isotopologue of CH. However, analysis and establishment of high-resolution line lists of 12 CH continues to be of interest [36].…”
Section: Emission-and Cavity Ring-down-spectra Of the A-x And B-x Bandsmentioning
confidence: 99%
“…YO shows avoided crossings between the B 2 Σ + , D 2 Σ + and A 2 Π, C 2 Π states as described by Yurchenko et al YO has broad scientific interest, having been observed in stellar spectra, and found use in solar furnaces , and magneto-optical traps. , YO is a complex system showing many low-lying electronic states; accurate descriptions of its avoided crossings will be valuable to works in several fields. CH is one of the most studied free radicals because it occurs in such a wide variety of environments: it has been observed in flames, , solar and stellar spectra, spectra of comets, ISM, and molecular clouds …”
Section: Introductionmentioning
confidence: 99%
“…60,61 YO is a complex system showing many low-lying electronic states; accurate descriptions of its avoided crossings will be valuable to works in several fields. CH is one of the most studied free radicals 62 because it occurs in such a wide variety of environments: it has been observed in flames, 63,64 solar 65−67 and stellar spectra, 68−70 spectra of comets, 71 ISM, 72−75 and molecular clouds. 76 As part of the study, we also report our implementation of the full diabatic/adiabatic treatments in our code DUO, 77 a rovibronic solver of general coupled diatomic Schrodinger equations, which is used in the analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation